Effect of Cr2O3 content on high-temperature dielectric properties and crystallisation of CMAS glass-ceramics. (24th April 2019) - Han, Yajing; Jia, Xiaolin; Liu, Fang; Deng, Leibo; Zhang, Xuefeng
Abstract: CaO–MgO–Al2 O3 –SiO2 (CMAS) glass-ceramics were prepared using fly ash and Bayan Obo West Mine tailings as the main raw materials by microwave heating. The effects of Cr2 O3 content on the structure and properties of the glass-ceramics were investigated by differential thermal analysis, x-ray diffraction, scanning electron microscopy, and physical and dielectric property analysis. Diopside was the main crystalline phase of the glass-ceramics, and Cr2 O3 evidently refined the grain size. The sample with 0.7 wt% Cr2 O3 showed the best dielectric properties. Moreover, the microwave absorption capacity of glass and degree of coupling between the sample and microwave was enhanced at 600 °C and various frequencies (2.6–4.0 GHz). With increase in the Cr2 O3 content, the density, bending strength, and Vickers hardness increased. The sample with 0.7 wt% Cr2 O3 exhibited the maximum bending strength (149.30 MPa) and Vickers hardness (796.32 kg · mm −2 ). All samples showed better alkali resistance (>98 %) than acid resistance.